Synthesis and characterization of graphene sheets decorated with carbon black by direct pyrolysis of a molasses-carbon black mixture as a potential versatile filler for rubber - Roy, A; Kar, S; Ghosal, R; Mukhopadhyay, R; Naskar, K; Bhowmick, A.K (Rubber Chemistry and Technology, 95(2): 277-279., 2022)
A mixture of molasses and carbon black was pyrolyzed in an inert atmosphere, which resulted in graphene of high quality, comprising of three to four layers on average with carbon black particles distributed over the graphene sheets. Molasses is the viscous dark colored slurry which is obtained at the last stage of refinement of sugar from sugarcane, in which sucrose is present as the major chemical component. Carbon black was also used as a substrate for the growth of graphene. The carbon black decorated graphene hybrid nanostructure was thoroughly characterized by different techniques and improved the failure properties of cured styrene butadiene rubber when incorporated into the rubber matrix. Bound rubber content increased by 50% with the hybrid filler compared to carbon black at 45 phr filler loading. The hybrid filler displayed 63% enhancement in the tensile strength at 2 phr filler loading and 86% increase at 45 phr filler loading, compared to the carbon black filled rubbers at the same loading. The vulcanizates containing the novel filler also exhibited improved abrasion resistance, ice traction, and wet traction and decreased rolling resistance compared to the carbon black filled systems. The new filler exhibited fair value of specific capacitance, 127 F/g when incorporated in an uncured rubber latex matrix. The hybrid filler synthesized, characterized, and studied thus can be classified as a versatile smart filler for rubber nanocomposites with a range of functionalities from mechanical reinforcement to electrochemical properties.
Keywords: Carbon black; Graphene sheets